Studies on martial arts, fights and sports combat with police: a systematic review - Jonatas Deivyson Reis Da Silva Duarte; Almir De França Ferraz (Scientific Electronic Archives, 2022)
The profession of a military police officer is to maintain order and that is why he may find himself in stressful and life-threatening situations. Although they undergo specific military training, martial arts, fighting and combat sports (MA/F/CS) is a recommended way to maintain health and additional training for these military police officers.  To analyze through a systematic review the studies carried out on MA/F/CS with police officers. Methods: The systematic search for this study was conducted through the Pubmed, Scielo, Lilacs, Medline and Portal de Periódicos da Capes (Brazilian indexing portal). Five articles were included that showed the relationship of how the MA/F/CS can improve the performance of police officers, reducing stress, anxiety, injuries and medical certificates. The regular practice of MA/F/CS as an additional form for police officers appears to improve the performance of their duties. However, future studies should analyze health and quality of life markers in this population.